Agrarian Governance – Who, What, Why, How, Where, When, Price, Level? - BACHEV, Hrabrin (Theoretical and Practical Research in Economic Fields, 2023)
The problem of understanding and evaluation of agrarian governance is among the most topical academic and practical tasks. However, there are huge differences in understandings of the governance among scholars, practitioners, official and business documents. Sometimes it is associated with the top management (country, organization); sometimes it is related to government agencies (public administration); sometimes it encompasses the management outside government entities; sometimes it is synonym of Management or a part of Management of organization, while in some case it is more general than Management including a variety of modes. This article adapts the New Institutional Economics methodology and proposes an adequate definition and framework for analyzing the system of agrarian governance. Based on a critical review of publications and experiences, the agrarian governance is understood as a complex system including: agrarian and related agents involved in making management decisions; rules, forms and mechanisms that govern behavior, activities and relationships of agrarian agents; processes and activities related to making governing decisions; a specific social order resulting from functioning of the system. Analysis includes individual elements for the system, different levels and main functional areas, for which adequate methods of institutional approach are suggested. Personal characteristics of participating agents, institutional environment, transaction costs and benefits, comparative efficiency of alternative governing structures, and "time factor" are considered. First holistic assessment found that Governance of Bulgarian agriculture is at moderate level having in mind EU perspective. Highest performance is attained for principles Equity and Solidarity and Good Working Public Sector while in terms of Working Private Sector and Stakeholders Involvements it is lowest.